Schorch, P., Saxer, M., & Elders, M. (org.). (2020). Exploring materiality and connectivity in Anthropology and beyond. Londres: UCL Press. 282 p. - Rochedo, Aline Lopes (Campos - Revista de Antropologia, 2021)
Resenha da coletânea Exploring materiality and connectivity in Anthropology and beyond, editada por Philipp Schorch, Martin Saxer e Marlen Elders, publicada em 2020.